Kajian Pengawasan Unit Apron Movement Control (AMC) terhadap Kelayakan Ground Support Equipment (GSE) di Sisi Udara Bandar Udara Internasional Hang Nadim Batam - Tandibua, Dian Bella; Widagdo, Djoko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Supervision conducted by Apron Movement Control (AMC) on the feasibility of Ground Support Equipment (GSE) vehicles is still frequently found in incidents and violations on the airside. Violations found such as damage to the vehicle engine, vehicle facilities that do not comply with regulations, and oil/fuel spills. This study aims to find out the causes of the lack of supervision of the Apron Movement Control (AMC) unit on the feasibility of the Ground Support Equipment (GSE) on the airside and to find out the reasons why Ground Support Equipment (GSE) vehicles that are not operationally feasible are still used on the air side at International Aiports Hang Nadim Batam. This study uses a qualitative method. Data collection techniques through interviews, observation and documentation. Then data analysis was carried out, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that direct supervision by Apron Movement Control (AMC) of GSE vehicles has not been carried out properly because AMC officers are more focused on garbarata services and Human Resources (HR) are limited, so violations are still found on the airside such us GSE vehicles that are not properly operational. Unfit GSE vehicles are still used for operational activities on the airside due to very busy flight schedules. Keywords: Supervision, Apron Movement Control (AMC), Feasibility, and Ground Support Equipment (GSE).